Vibration Analysis to Detect Failure Bearing of Centrifugal Pump “Black Liquor Pump” in PT. Riau Andalas Pulp & Paper (RAPP) - Irwan Anwar; Afdal (Jurnal Teknik Mesin, 2021)
Bearing is one of machine element specialized to hold the load both radial and thrust load, also in supporting the shaft while operating. Because of a factor such as friction that occurred between bearing and shaft It would be influencing to machine’s performance is totally dependent to the currently used bearing and inefficiently operation. This research’s aim was to be analyzed what kind of failure and detected the cause of it failures that appear influencing to the bearing life time. The method used to research of that failures using relevant update issue such as literature study, surveying, collecting data. The result of this researching showed the cause of that bearing failure was happened at the cage of bearing and broken of bearing ring. Furthermore, supervising by control of a good maintenance schedule, making influence to the effect of load on reliability. So the remaining life of bearing had been investigated, showing that a potential decrease in remaining life significantly.